Analisis Pengaruh Iklim Organisasi, Pengawasan, dan Kompetensi Pegawai Terhadap Kinerja Pegawai di Kantor Kelurahan Pondok Cina Kota Depok - Anggraeni, Dessi; Latunreng, Wahyuddin; Ludfi Arifin, Antoni (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research is about organizational climate, supervision, and competence claims that can improve employee performance at the Pondok Cina Subdistrict Office, Depok City. The goal of this research is to analyze and evaluate how much influence organizational, supervision, and competence claims have on employee performance either partially or simultaneously. Population and sample of this study were 50 workers. The independent variables in this research are Organizational Climate (X1), Supervision (X2), and Competence (X3) while the dependent variable is Employee Performance (Y). Data analysis in this study used SPSS Version 25. Based on this research, the t test of the influence of Organizational Climate (X1) on Employee Performance (Y) has a magnitude of 0.251 or 25.1%. Then the influence of Supervision (X2) on Employee Performance (Y) with the magnitude of the influence being 0.224 or 22.4%. Furthermore, the influence of Employee Competency (X3) on Employee Performance (Y) with the magnitude of the influence is 0.285 or 28.5%. Meanwhile, Organizational Climate (X1), Supervision (X2), and Competency (X3) simultaneously on Employee Performance (Y) is 0.414 or 41.4%.